Civil empowerment of sanitation latrine for urban life society: Human resource development perspective - Uripan, Koen Irianto; Sri Iswat, Subagyo Adam, Falih Suaedi; Trisliatanto, Dimas Agung (Opción, 1970)
purpose of this study is to identify the civil empowerment of sanitation latrine for urban life society by human resource development perspective through industrial revolution 4.0. The results of this study indicated that community empowerment carried out in connection with the handling of latrine sanitation had these four aspects that should contribute to the creation of the aspirations of the self-reliant community because then the community would occur the adequacy of insights complemented by sufficient skills, reinforced by a sense of need for development and a conscious behavior towards these needs, to achieved community independence require a process